A study on the difference in voting behavior of Filipinos in relation to political influence moderated by political maturity - Chingkoe, Mariah Claire D. (Animo Repository, 2016)
The study aimed to answer three questions: to find out whether a person's status as a first-time or long-time voter affected their voting behavior, whether political influence had any effect on voting behavior between first-time or long-time voters with regard to social influence and/or the candidate qualifications, and if Political Maturity was an effective moderator between political influence and voting behavior. Results reveal that the latter two were deemed significant.